Protective role for caspase-11 during acute experimental murine colitis. - O'NEILL, LUKE; RAVERDEAU, MATHILDE; MILLS, KINGSTON; CREAGH, EMMA; CORR, SINEAD (My University, 2015)
Activation of the noncanonical inflammasome, mediated by caspase-11, serves as an additional pathway for the production of the proinflammatory cytokines IL-1β and IL-18. Noncanonical inflammasome activity occurs during host defense against Gram-negative bacteria and in models of acute septic shock. We propose that the noncanonical inflammasome is activated in mice during acute intestinal inflammation elicited by dextran sodium sulfate (DSS), a model of experimental colitis. We find that caspase-11−/− mice display enhanced susceptibility to DSS, because of impaired IL-18 production. The impaired IL-18 levels observed are shown to result in reduced intestinal epithelial cell proliferation and increased cell death. We also suggest that a novel type II IFN–dependent, type I IFN-TRIF–independent signaling pathway is required for in vivo caspase-11 production in intestinal epithelial cells during DSS colitis. Collectively, these data suggest that IFN-γ–mediated caspase-11 expression has a key role maintaining intestinal epithelial barrier integrity in vivo during experimentally induced acute colitis.
PUBLISHED
Keywords: caspase-11; caspase-11; Immunology, Inflammation & Infection